A new nucleolar body appears in Drosophila saltans salivary gland cells before histolysis, in programmed cell death - de Oliveira, C. C.; Bicudo, H. E. M. de Campos (Univ Arizona, 2006)
The salivary glands of Drosophila saltans ( saltans group, saltans subgroup) analyzed in an advanced stage of programmed cell death showed the appearance of a single, round, nucleolar corpuscle inside the highly altered nucleus of every gland cell, at a time during which the integrity of the original nucleolus was already lost and the original nucleolar material apparently disappeared. In the same nuclei, which already had also lost the characteristic chromosome structure, some delicate chromosome threads were maintained. In many cells, the new nucleolar corpuscle and these chromosome threads are associated. These findings are novel. However, the hypothesis put forward concerning their meaning remains dependent on other studies.
Keywords: salivary gland; nucleolar and chromosome changes in cell death; Drosophila saltans